LRRK2 Regulates Voltage-Gated Calcium Channel Function - Bedford, Cade; Sears, Catherine; Perez-Carrion, Maria; Piccoli, Giovanni; Condliffe, Steven B. (Frontiers in Molecular Neuroscience, 2016)
Voltage-gated Ca2+ (CaV) channels enable Ca2+ influx in response to membrane depolarization. CaV2.1 channels are localized to the presynaptic membrane of many types of neurons where they are involved in triggering neurotransmitter release. Several signaling proteins have been identified as important CaV2.1 regulators including protein kinases, G-proteins and Ca2+ binding proteins. Recently, we discovered that leucine rich repeat kinase 2 (LRRK2), a protein associated with inherited Parkinson’s disease, interacts with specific synaptic proteins and influences synaptic transmission. Since synaptic proteins functionally interact with CaV2.1 channels and synaptic transmission is triggered by Ca2+ entry via CaV2.1, we investigated whether LRRK2 could impact CaV2.1 channel function. CaV2.1 channel properties were measured using whole cell patch clamp electrophysiology in HEK293 cells transfected with CaV2.1 subunits and various LRRK2 constructs. Our results demonstrate that both wild type LRRK2 and the G2019S LRRK2 mutant caused a significant increase in whole cell Ca2+ current density compared to cells expressing only the CaV2.1 channel complex. In addition, LRRK2 expression caused a significant hyperpolarizing shift in voltage-dependent activation while having no significant effect on inactivation properties. These functional changes in CaV2.1 activity are likely due to a direct action of LRRK2 as we detected a physical interaction between LRRK2 and the β3 CaV channel subunit via coimmunoprecipitation. Furthermore, effects on CaV2.1 channel function are dependent on LRRK2 kinase activity as these could be reversed via treatment with a LRRK2 inhibitor. Interestingly, LRRK2 also augmented endogenous voltage-gated Ca2+ channel function in PC12 cells suggesting other CaV channels could also be regulated by LRRK2. Overall, our findings support a novel physiological role for LRRK2 in regulating CaV2.1 function that could have implications for how mutations in LRRK2 contribute to Parkinson’s disease pathophysiology.